Mixed Methods Approach In Business Management Research: Advantages And Applications In An Organizational Context - Kurniawati, Hasni Dyah; Saefudin, Saefudin (Institute of Computer Science (IOCS), 2025)
This article aims to explore the theoretical foundations, applications, and benefits of mixed methods in business management by highlighting its philosophical foundations in pragmatism and its ability to integrate diverse perspectives. This article uses qualitative techniques with a literature review approach to mixed methods research in business management. The results of this study highlight the importance of methodological pluralism in overcoming biases and limitations of single-method designs. Practical applications of mixed methods in business management research include their use in understanding organizational complexity, refining decision-making processes, and enhancing research instrument development. Despite challenges such as integration difficulties and resource requirements, mixed methods research offers unparalleled potential to address complex business management problems and foster innovative and actionable solutions.